2020
DOI: 10.1002/er.5674
|View full text |Cite|
|
Sign up to set email alerts
|

Carbon‐based nanocomposites in solid‐state hydrogen storage technology: An overview

Abstract: Hydrogen fuel is becoming a hot topic among the scientific community as an alternative energy source. Hydrogen is eco-friendly, renewable, and green. The synthesis and development of materials with great potential for hydrogen storage is still a challenge in research and needs to be addressed to store hydrogen economically and efficiently. Various solid-state materials have been fabricated for hydrogen energy storage; however, carbon-based nanocomposites have gained more attention because of its high surface a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 133 publications
(197 reference statements)
0
25
0
Order By: Relevance
“…However, the result indicated that Fe-Ag/TiO2/ MWCNT nanocomposite prepared with 0.04 M bimetallic Fe-Ag nanoparticles increases the multiwall carbon nanotubes hydrogen uptake significantly. 46 Recently, Salehabadi et al 47 published a review on carbon-based nanocomposites synthesized with metals/CNTs, graphene oxide (GO), and rGO for hydrogen storage. The unique properties of carbon materials make them suitable as reinforcement or filler for metals, metal oxides, and organometallic frameworks with high hydrogen storage capacity.…”
Section: Hydrogen Storage Materialsmentioning
confidence: 99%
“…However, the result indicated that Fe-Ag/TiO2/ MWCNT nanocomposite prepared with 0.04 M bimetallic Fe-Ag nanoparticles increases the multiwall carbon nanotubes hydrogen uptake significantly. 46 Recently, Salehabadi et al 47 published a review on carbon-based nanocomposites synthesized with metals/CNTs, graphene oxide (GO), and rGO for hydrogen storage. The unique properties of carbon materials make them suitable as reinforcement or filler for metals, metal oxides, and organometallic frameworks with high hydrogen storage capacity.…”
Section: Hydrogen Storage Materialsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Hydrogen is widely applied in many reams, such as nickel-hydrogen batteries, fuel cells, and hydrogen-powered vehicles. [13][14][15] There are three stages in the hydrogen energy supply chain: hydrogen preparation, hydrogen storage and transportation, and hydrogen applications. [16][17][18][19] To develop a safe and efficient hydrogen storage system with high energy density remains an enormous challenge.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25][26] Besides, the electrochemical hydrogen storage also possesses the merits of simplicity, reusability and safety. 27 The mechanism of electrochemical storage contains a few steps as described below: [13][14][15]24,[28][29][30][31] I. In the electrochemical reduction process (charging): when the electrons are transferred from the carbon electrode to the H 2 O molecules in the electrolyte at electrode/electrolyte interface, isolated H atoms are formed and adsorbed on the electrode surface (Volmer reaction).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations